(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
The aim of this paper is to propose a comparison between the mystical feeling, as it is defined by Ludwig Wittgenstein in the Tractatus logico-philosophicus, and the psycho-pathological state of melancholy, posed in relation with mourning by Sigmund Freud. The comparison will depart from the radical dissatisfaction that seems to be a distinctive characteristic of both phenomena. According to Wittgenstein in fact the drive to mystical feeling rises from the deep dissatisfaction regarding the explanations given by science, which is incapable of producing any answer to the «problem of life». In a similar way, Slavoj Žižek underlines that melancholy is a form of «disappointment at all positive, observable objects, none of which can satisfy our desire». In this perspective, I will check the similarities and differences between mystical feeling and melancholy and I will put in relation the double profile of this latter (manic depression) with the Wittgensteinian theme of aspect seeing («seeing-as»).